2012
DOI: 10.5539/ijc.v4n2p38
|View full text |Cite
|
Sign up to set email alerts
|

A Pt3Sn/C Electrocatalyst Used as the Cathode and Anode in a Single Direct Ethanol Fuel Cell

Abstract: This paper presents a study involving the use of Pt 3 Sn/C electrocatalysts as cathodes and anodes in a single direct ethanol fuel cell. First, we studied the oxygen reduction reaction (ORR) using commercial Pt/C from ETEK and Pt 3 Sn/C as electrocatalysts with an alloy degree of 92 %. The electrocatalytic activity of the material for oxygen reduction was assessed using the rotating disk electrode technique (RDE). When Pt 3 Sn was tested for ORR in the presence of ethanol, the results showed greater tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Soc. 1092 Thus, Wongyao et al 23 suggested that different proportions of PtSn/C can be used as electrocatalysts because an anode composed of this material will selectively adsorb ethanol.Taking into account previous studies, 14,24,25 PtSn/C (3:1) with an alloy degree of approximately 92% was one of the best materials reported for ethanol oxidation. Additionally, to optimize the DAFC performance using mixed alcohols (i.e., ethanol and methanol) the electrocatalyst used for the anode must selectively adsorb an alcohol, especially ethanol (e.g., PtSn/C (3:1)).…”
mentioning
confidence: 99%
“…Soc. 1092 Thus, Wongyao et al 23 suggested that different proportions of PtSn/C can be used as electrocatalysts because an anode composed of this material will selectively adsorb ethanol.Taking into account previous studies, 14,24,25 PtSn/C (3:1) with an alloy degree of approximately 92% was one of the best materials reported for ethanol oxidation. Additionally, to optimize the DAFC performance using mixed alcohols (i.e., ethanol and methanol) the electrocatalyst used for the anode must selectively adsorb an alcohol, especially ethanol (e.g., PtSn/C (3:1)).…”
mentioning
confidence: 99%